Cognitive Processes in Discourse Comprehension: Passive Processes, Reader-Initiated Processes, and Evolving Mental Representations. Issue 5 (4th July 2017) - van den Broek, Paul; Helder, Anne
ABSTRACT: As readers move through a text, they engage in various types of processes that, if all goes well, result in a mental representation that captures their interpretation of the text. With each new text segment the reader engages in passive and, at times, reader-initiated processes. These processes are strongly influenced by the readers' representation of the preceding text and, in turn, update this very same representation. This updated representation forms the backdrop for the processing of the next text segment, and so on. Thus, passive and reader-initiated processes and the evolving representation engage in a continual, intricate interaction as the reader moves through the text. We provide a framework for conceptualizing the interplay between these three components of comprehension and propose that (1) passive and reader-initiated processes interact during reading; (2) a reader's standards of coherence moderate what kind and to what extent reader-initiated processes take place; (3) reader-initiated processes lie along a continuum from close-to-the-text, coherence-building processes to far-from-the-text, interpretive processes; and (4) the moment-to-moment processes and the evolving mental representation interact in a reciprocal fashion. We present results from recent experiments on key aspects of the framework, and identify questions the framework raises. We conclude with implications from this conceptualization for theoretical models of reading comprehension.